Enhancement of local area DGPS accuracy: a composite approach - Che Awang, M. Saupi; Subari, Mustafa Din (2005)
In a conventional Local Area DGPS (LADGPS) operation, the user’s receiver (rover) is set to receive signals from a nearest beacon (base) that provides signals meeting the appropriate standard, with the second-nearest acting as alternate. The reason for choosing the nearest beacon is that the accuracy of fixes (i.e. the position of user) is dominated by spatial dilution of precision (DOP) of the corrections. The degree of dilution increases with the distance of the rover from the base. In other words, the accuracy of the single base LADGPS service degrades as the users move away from the beacon. This is the major drawback of a single base LADGPS system. This paper attempts to highlight an approach that is being studied to minimize the spatial errors in the LADGPS system, hence enhancing the positioning accuracy provided by the service.